Improving the tensile and flexural properties of reinforced epoxy composites by using cobalt filled and carbon/glass fiber - Dipen Kumar Rajak; Pratiksha H. Wagh; Hassan Moustabchir; Catalin I. Pruncu (Forces in Mechanics, 2021)
ABSTRACT: In this paper, the study concentrates on the flexural and tensile characteristics of the cobalt filler and fiber-reinforced epoxy composites used in the car body parts. Glass fiber (GF) and carbon fiber (CF) filled with the epoxy compound were prepared by hand lay-up varying the percentage of weight (wt.%) of cobalt from (0.4 to 1.0 wt.%). GF tensile and flexural strength were available at approximately 96.9 MPa and 120 MPa, respectively, while tensile and flexural strength of the reinforced CF was combined found in 194.82 MPa and 393.34 MPa. A 55.64% increase in flexural and tensile strength of the specimen was obtained compared to pure epoxy which represents a significant improvement. The use of a 0.6 wt.% Cobalt (Co) filler content for the combination of GF and CF epoxy reinforces positive results in the strength test. In addition, Field Emission Scanning Electron Microscopy (SEM) was done to investigate the microstructural characterization, the performance of GF and CF epoxy reinforced composite.